Problems of improvement of the mechanism of a sustainable development of the industrial enterprises on the basis of formation of the competitive environment (Путеводитель предпринимателя, 2020)
Article is devoted to problems of improvement of the mechanism of a sustainable development of the industrial enterprises on the basis of formation of the competitive environment.